2010
DOI: 10.1186/1748-717x-5-83
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of volumetric modulated arc therapy for the treatment of retroperitoneal sarcomas

Abstract: BackgroundRadiotherapy for retroperitoneal sarcomas remains controversial and a technical challenge considering the threshold of contiguous critical organs tolerance. We performed consecutive RapidArc dosimetric plans in preoperative or postoperative setting.MethodsA dosimetric study was carried out from six preoperative (group A) and four postoperative (group B) CT-scans, performed in 7 patients.Prescribed dose was 45 and 50 Gy for groups A and B, respectively. The planning target volume (PTV) was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…The homogeneity index (D2%D98%D50%false) was 0.068 and 0.066 for VMAT and IMRT, respectively. This is comparable to earlier reported RPS studies (D5%–D95%) . .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The homogeneity index (D2%D98%D50%false) was 0.068 and 0.066 for VMAT and IMRT, respectively. This is comparable to earlier reported RPS studies (D5%–D95%) . .…”
Section: Discussionsupporting
confidence: 92%
“…VMAT is an improved and more efficient method of delivering IMRT as demonstrated for other tumor sites . A single feasibility study investigating the use of VMAT for treatment of RPS is reported; however, they did not perform a direct comparison of VMAT to IMRT as it has been done for other tumor sites. Therefore, it is important to conduct and report dosimetric comparison studies of VMAT and IMRT in RPS, such that evidence can guide adoption of this technique in clinical practice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…VMAT plans achieved better conformity and OAR sparing (left kidney, liver, stomach, small bowel and duodenum) compared with fixed field IMRT (SW). Llacer-Moscardo et al [150] performed a dosimetric feasibility study of VMAT in retroperitoneal sarcoma and found acceptable target volume coverage and OAR sparing. Benthuysen et al [151] evaluated VMAT in distal oesophageal cancers and found comparable PTV coverage and OAR sparing to fixed field IMRT with a 42-67% reduction in MU, but greater low dose radiation to the body (V5 Gy 18% greater for VMAT plans).…”
Section: Intra-abdominal Tumoursmentioning
confidence: 99%
“…Many indications can benefit from the RA technology, and, regarding sarcomas, little has been published to date. LlacerMoscardo et al [11] investigated the potential of this VMAT approach for huge retroperitoneal sarcoma, this being the seminal study for the application of the new treatment technique to this class of tumours. A more recent study [12] assessed the positive role of RA in the case of soft-tissue sarcoma in the legs with the possibility of significantly sparing the femurs.…”
Section: Advances In Knowledgementioning
confidence: 99%